Manajemen Resiliensi Remaja Pada Keluarga Single Parent dari Perceraian - Achmad Faridul Ilmi (Kuras Institute, 2022)
The focus of the problem in this study is how the resilience of adolescents who come from single parent families from divorce in Sukomaju Village, Banyuwangi Regency and what efforts are made by teenagers to increase resilience in Sukomaju Village, Banyuwangi Regency, the purpose of this study is to determine the resilience of adolescents in single parent families. from divorce in Sukomaju Village, Banyuwangi Regency and to find out the efforts made by teenagers in increasing resilience in Sukomaju Village, Banyuwangi Regency. This research uses qualitative research with descriptive method. Methods of collecting data through observation, interviews and documentation. The results of this study can be concluded that adolescents in single parent families from divorce in Sukomaju Village, Banyuwangi Regency have good resilience. Good resilience can be seen from several indicators, namely willingness to serve others, use life skills, sociability, have a sense of humor, internal locus of control, autonomy, have a positive view of the future, flexibility, have the capacity to continue learning, self-motivated, personal competence, have self-esteem and self-confidence. Meanwhile, efforts made to increase resilience are emotion regulation, impulse control, optimism, analysis of the causes of problems, empathy, self-efficacy, and reaching out.